EFFECT OF ILOGEN EXCEL ON LIPIDS IN EXPERIMENTALLY INDUCED DIABETES MELLITUS. - Jansi Rani s, Lucia (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The present study was used to evaluate the anti hyper lipidemic effect and anti oxidant effect of Ilogen Excelâ€ and ayurvedic herbal formulation in experimentally induced diabetic rats. Increase in the level of blood glucose, decrease in the level of plasma insulin, increase in the concentration of lipids in the heart and brain were registered in STZ induced diabetic rats when compared to normal rats. Oral administration of Ilogen excel 100 mg/kg daily for a period of two months to diabetic rats decreased the levels of Cholesterol, TGL, FFAS, PLS in heart and brain of diabetic rats . Thus our study shows anti hyper lipedimic effect of Ilogen Excel in STZ induced diabetic rats. Keywords: Anti hyperlipidemic, Anti oxidant, Free fatty acids (FFAS), Phospholipids (PLS) , Streptozotocin (STZ)